Comprehensive Analysis of Cyclin Family Gene Expression in Colon Cancer - Li, Jieling; Zhou, Liyuan; Liu, Ying; Yang, Lingzhi; Jiang, Dayi; Li, Kuan; Xie, Shouxia; Wang, Xiao; Wang, Shaoxiang (Frontiers in Oncology, 2021)
Colon cancer is a common malignancy of the digestive tract with high morbidity and mortality. There is an urgent need to identify effective biomarkers for the early diagnosis of colon cancer and to prolong patient survival. Cyclins are a family of proteins that directly participate in the cell cycle and are associated with many types of tumors, but the role and regulatory mechanism of most cyclin family members in colon cancer remain unclear. Here, we provide a systematic and comprehensive study of cyclin family gene expression and their potential roles in colon cancer. Pan-cancer analysis revealed that cyclin genes were most differentially expressed in colon adenocarcinoma. Among the four datasets of colon cancer from The Cancer Genome Atlas and the Gene Expression Omnibus, six cyclin genes (CCNA2, CCNB1, CCND1, CCNE1, CCNF, and CCNJL) were differentially expressed between normal and tumor tissues. Four of them (CCNA2, CCNB1, CCNE1, and CCNF) were notably elevated in the early TNM stages and significantly correlated with overall patient survival. Meanwhile, the expression of CCNA2 and CCNB1 was positively correlated with tumor-killing immune cells, such as CD8+ T cells.The copy numbers of CCNA2, CCNB1, CCND1, CCNE1, and CCNF was positively related to gene expression. The methylation levels of CCNB1 were lower in tumor tissues than in normal tissues and were negatively correlated with gene expression. The receiver operating characteristic curves indicated that the gene expression of 24 cyclins had higher predictive accuracy than the TNM stage. Pathway analysis showed that cyclin genes were tightly associated with apoptosis, the cell cycle, hormone ER, the RAS/MAPK pathway, mismatch repair, mTORC1 signaling, KRAS signaling, Akt, and TGFB in colon cancer. Weighted gene co-expression network analysis suggested that cyclin genes were closely linked to CDK1, BIRC5, PLK1, and BCL2L12. At the protein level, Cyclin A2 and Cyclin B1 were also expressed higher in colon adenocarcinoma tissues. In addition, cyclin genes were highly related to the drug sensitivity of some FDA-approved drugs, such as MEK and EGFR inhibitors, which might provide guidance for clinical treatment. In conclusion, cyclin genes are promising biomarkers for the diagnosis and prognosis of colon cancer.